دور التحول الرقمي في تحسين أداء الوظيفة العامة دراسة ميدانية على القيادات الإدارية بصندوق الضمان الاجتماعي فرع الزاوية (Comprehensive Journal of Science, 2025)
This study aimed to examine and explore the role of digital transformation in improving public job performance, with application at the Social Security Fund – Al-Zawiya Branch and its affiliated offices. To achieve this objective, a main hypothesis was formulated, branching into three sub-hypotheses, in preparation for identifying this role in enhancing public job performance. The research was conducted through a comprehensive survey of the entire population, consisting of 34 members from the administration, departments, and main and sub-units. A questionnaire was used as the primary tool for collecting field data and information, and statistical analysis was performed using the SPSS statistical software.The study found a significant relationship between the dimensions of digital transformation and improved job performance, as well as a positive (direct) correlation between these dimensions and enhanced public job performance. These findings highlight that the Social Security Fund possesses modern technical devices and systems that contribute to developing the necessary skills for performing job tasks effectively, and that their utilization helps streamline and shorten procedural steps in workflow processes.The study recommended the need to develop and activate integrated electronic channels for delivering services to beneficiaries, leveraging the available modern technical devices and systems to enhance performance efficiency, improve beneficiaries’ experience, and keep pace with digital transformation in the delivery of government services.
Keywords: Digital Transformation, Public service performance